USE OF THE SCIENTIFIC AND CREATIVE HERITAGE OF EASTERN THINKERS FOR EDUCATIONAL PURPOSES - Saidaliev Saidumar; Mamatova Nasibaxon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article presents scientific facts on the implementation of radical reforms in all areas after the independence of the Republic, as well as restoration of our spiritual and cultural heritage, national values.